Incidence of seizure exacerbation and seizures reported as adverse events during adjunctive treatment with eslicarbazepine acetate: A pooled analysis of three Phase III controlled trials. Issue 4 (9th November 2017) - Carreño, Mar; Benbadis, Selim; Rocha, Francisco; Blum, David; Cheng, Hailong
Summary: Objective: To investigate whether adjunctive eslicarbazepine acetate (ESL) could lead to exacerbation of seizures in some patients. Methods: Post‐hoc analysis of data pooled from three Phase III trials of adjunctive ESL (studies 301, 302, and 304) for refractory partial‐onset seizures (POS). Following an 8‐week baseline period, patients were randomized to receive placebo or ESL 400, 800, or 1, 200 mg once daily (2‐week titration, 12‐week maintenance, 2–4 week tapering‐off periods). Patient seizure diary data and seizure treatment‐emergent adverse event (TEAE) reports were pooled for analysis. Results: The modified intent‐to‐treat and safety populations comprised 1, 410 patients and 1, 447 patients, respectively. Titration period : Compared with placebo (32/21%), significantly smaller proportions of patients taking ESL 800 mg (20/15%) and 1, 200 mg (22/12%) had a ≥25/≥50% increase in standardized seizure frequency (SSF) from baseline; there was no significant difference between placebo and ESL 400 mg. Maintenance period : Compared with placebo (20%), significantly smaller proportions of patients taking ESL (400 mg, 12%; 800 mg, 12%; 1, 200 mg, 14%) had an increase in SSF ≥25%. When evaluating ≥50% increases in SSF, only ESL 800 mg (7%) was significantly different from placebo (12%). Some patients had no secondarily generalized tonic‐clonic (sGTC) seizures during baseline but had ≥1 sGTC seizure during maintenance treatment (placebo, 11%; ESL 400 mg, 5%; 800 mg, 10%; 1, 200 mg, 5%). Fewer patients had a ≥25% increase in sGTC seizure frequency with ESL (400 mg, 11%; 800 mg, 9%; 1, 200 mg, 14%) versus placebo (19%). The incidence of seizures reported as TEAEs was low in all treatment groups; incidences were generally lower with ESL versus placebo. Tapering‐off period : Similar proportions of patients taking ESL and placebo had a ≥25/≥50% increase in SSF. Seizure TEAE incidence was numerically higher with ESL versus placebo. Significance: Treatment with adjunctive ESL does not appear to aggravate POS or sGTC seizures.